Evaluation of various conventional methods for sampling weeds in potato and spinach crops (2014)
This study aimed to evaluate (at an exploratory level), some of the different conventional sampling designs in a section of a potato crop and in a commercial crop of spinach. Weeds were sampled in a 16 x 48 m section of a potato crop with a set grid of 192 sections. The cover and density of the weeds were registered in squares of from 0.25 to 64 m2. The results were used to create a database that allowed for the simulation of different sampling designs: variables and square size. A second sampling was carried out with these results in a spinach crop of 1.16 ha with a set grid of 6 x 6 m cells, evaluating the cover in 4 m2 squares. Another database was created with this information, which was used to simulate other sampling designs such as distribution and quantity of sampling squares. According to the obtained results, a good method for approximating the quantity of squares for diverse samples is 10-12 squares (4 m2) for richness per ha and 18 or more squares for abundance per hectare. This square size is optimal since it allows for a sampling of more area without losing sight of low-profile species, with the cover variable best representing the abundance of the weeds.